Sources of intraspecific variation in the collective tempo and synchrony of ant societies. (11th August 2019) - Doering, Grant Navid; Sheehy, Kirsten A; Lichtenstein, James L L; Drawert, Brian; Petzold, Linda R; Pruitt, Jonathan N
Abstract: Populations of independently oscillating agents can sometimes synchronize. In the context of animal societies, conspicuous synchronization of activity is known in some social insects. However, the causes of variation in synchrony within and between species have received little attention. We repeatedly assessed the short-term activity cycle of ant colonies ( Temnothorax rugatulus ) and monitored the movements of individual workers and queens within nests. We detected persistent differences between colonies in the waveform properties of their collective activity oscillations, with some colonies consistently oscillating much more erratically than others. We further demonstrate that colony crowding reduces the rhythmicity (i.e., the consistent timing) of oscillations. Workers in both erratic and rhythmic colonies spend less time active than completely isolated workers, but workers in erratic colonies oscillate out of phase with one another. We further show that the queen's absence can impair the ability of colonies to synchronize worker activity and that behavioral differences between queens are linked with the waveform properties of their societies. Abstract : Rhythmic oscillations of activities are a basic part of most animal's lives (e.g., circadian rhythms). Several species of ants, however, exhibit cycles of activity and inactivity at a period of only a few dozen minutes. We investigated what factors predict differences in the waveform properties of ant colonies' activity cycles. We found that there were stable differences between colonies and that the removal of queens desynchronized the activity cycles of their groups.